Polyhydroxyalcanoates of strains of Azospirillum spp. isolated of roots of Lycopersicon esculentum Mill. “tomato” and Oryza sativa L. “rice” in Lambayeque - Baca, Katty (2010)
In this work was determined the concentration of polyhydroxyalkanoates (PHAs) of Azospirillum strains isolated from roots of Lycopersicon esculentum Mill "tomato" and Oryza sativa L. "rice" as an alternative to accumulation of petroleum-based plastics. Previously disinfected root were plated in Nfb semisolid medium where nitrogen-fixing bacteria were recognized by a whitish film on the surface and turn from green to blue. The genus Azospirillum was identified in Congo red agar medium, obtained 96 isolates of A. lipoferum and A. brasilense on tomato and rice. Batch fermentation was performed with broth Azotobacter modified feeding a saturated solution of malic acid every 12 hours and were stained with Sudan Black B. Strains were selected with the greatest number of PHAs granules (in tomato, 18 of A. lipoferum and 2 of A. brasilense; in rice, 10 of A. lipoferum and 10 of A. brasilense ) and quantified the biomass and PHAs. PHAs concentration reached 0.661 gL-1 in A. lipoferum KM(T)-73 and 0.738 gL-1 in A. brasilense KM(T)-19, both isolated from tomato. Strains of A. lipoferum and A. brasilense isolated from tomato reached a higher concentration of biomass and PHAs against the strains of rice.